2015
DOI: 10.1101/gad.263574.115
|View full text |Cite
|
Sign up to set email alerts
|

miR-431 promotes differentiation and regeneration of old skeletal muscle by targeting Smad4

Abstract: The myogenic capacity of myoblasts decreases in skeletal muscle with age. In addition to environmental factors, intrinsic factors are important for maintaining the regenerative potential of muscle progenitor cells, but their identities are largely unknown. Here, comparative analysis of microRNA (miRNA) expression profiles in young and old myoblasts uncovered miR-431 as a novel miRNA showing markedly reduced abundance in aged myoblasts. Importantly, elevating miR-431 improved the myogenic capacity of old myobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 56 publications
4
86
0
Order By: Relevance
“…Consistent with previous reports, Smad4 disruption did promote myogenic terminal commitment (Dey et al, 2012; Ono et al, 2011; Lee et al, 2015). However, declines in proliferating SCs and MPs during regeneration were also observed.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous reports, Smad4 disruption did promote myogenic terminal commitment (Dey et al, 2012; Ono et al, 2011; Lee et al, 2015). However, declines in proliferating SCs and MPs during regeneration were also observed.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that knockdown of Smad4 or TGFβ superfamily ligand supplementation in myogenic cells is able to promote or impair terminal myogenic commitment, respectively (Ono et al, 2011; Dey et al, 2012; Lee et al, 2015; Trendelenburg et al, 2009). To examine the terminal myogenic fate decisions of Smad4-deficient SCs, FACs-purified adult P7:S4KO and Ctl SCs and MPs were cultured for 96 hr in plating media (10% horse serum, FGF2, DMEM), and supplemented with vehicle, TGFβ1, or BMP4 ligands (Chakkalakal et al, 2012, 2014; Zammit et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through this broad impact on gene expression, microRNAs can regulate diverse physiologic processes such as embryonic development and cell proliferation, differentiation, and apoptosis [4145]. Many microRNAs have also been implicated in pathological conditions including cancer, diabetes, cardiovascular disease, neurodegeneration, and immune diseases [4648].…”
Section: Micrornasmentioning
confidence: 99%